Comparative study between chitin/polyacrylic acid (paa) dressing, lipido-colloid absorbent dressing and alginate wound dressing: A pilot study in the treatment of partial-thickness wound - Apichai Angspatt (2018)
Background: Polyacrylic acid grafted chitin (Chitin-PAA) contains a hydrogel characteristic that makes it more suitable for wound dressing application. In animal models, Chitin-PAA dressing exhibited properties as a promising dressing. Epithelization promotion, rapid reduction of wound size, reduction of inflammatory cell response, and less toxicity had been noted. Objective: Carryout a pilot clinical comparative study of Chitin-PAA dressing, lipido-colloid absorbent dressing, and alginate wound dressing in the treatment of partial-thickness wound. Material and Method: Between June 2006 and March 2007, 36 partial-thickness wounds were randomized into three groups and three different types of dressing were used. Each wound was treated until it was completely healed, and a visual analogue scale was used for the pain evaluation. Result: The present study shows the visual analogue pain score in the Chitin-PAA group seems to be a bit higher than the Urgocell®group but not statistically different. The completely healed day is not significantly different. Three patients in the lipido-colloid absorbent dressing groups had wound infection but eventually healed after treatment. Conclusion: There was no statistical difference in terms of visual analogue pain score and healing time between the lipido- colloid absorbent dressing, alginate dressing, and chitin-PAA dressing.